Bahasa Inggris - Nurul Salamah; Tri Hesti Utaminingtyas; Achmad Fauzi (Yayasan Education and Social Center, 2023)
This study aims to determine the effect of Financial Distress, Profitability and Leverage on Accounting Conservatism in Manufacturing Companies on the Indonesia Stock Exchange for the 2017-2021 Period. The research method used is quantitative, with secondary data obtained from financial statements on the Indonesia Stock Exchange with a total sample of 58 companies using the purposive sampling technique. The data analysis technique used is descriptive statistical analysis, multiple linear regression analysis, analysis prerequisite test, classical assumption test and hypothesis testing. The results show that financial distress and leverage significantly negatively affect accounting conservatism, while profitability does not. The coefficient of determination in this study is 11.2% which offers the ability of financial distress, profitability and leverage to explain its impact on accounting conservatism. In contrast, the rest is explained by other variables